'Moving on' Violence, wellbeing and questions about violence in antenatal care encounters. A qualitative study with Somali-born refugees in Sweden. (September 2016) - Byrskog, Ulrika; Essén, Birgitta; Olsson, Pia; Klingberg-Allvin, Marie
Abstract: Background: Somali-born women constitute one of the largest groups of childbearing refugee women in Sweden after more than two decades of political violence in Somalia. In Sweden, these women encounter antenatal care that includes routine questions about violence being asked. The aim of the study was to explore how Somali-born women understand and relate to violence and wellbeing during their migration transition and their views on being approached with questions about violence in Swedish antenatal care. Method: Qualitative interviews (22) with Somali-born women (17) living in Sweden were conducted and analysed using thematic analysis. Findings: A balancing act between keeping private life private and the new welfare system was identified, where the midwife's questions about violence were met with hesitance. The midwife was, however, considered a resource for access to support services in the new society. A focus on pragmatic strategies to move on in life, rather than dwelling on potential experiences of violence and related traumas, was prominent. Social networks, spiritual faith and motherhood were crucial for regaining coherence in the aftermath of war. Dialogue and mutual adjustments were identified as strategies used to overcome power tensions in intimate relationships undergoing transition. Conclusions: If confidentiality and links between violence and health are explained and clarified during the care encounter, screening for violence can be more beneficial in relation to Somali-born women. The focus on "moving on" and rationality indicates strength and access to alternative resources, but needs to be balanced against risks for hidden needs in care encounters. A care environment with continuity of care and trustful relationships enhances possibilities for the midwife to balance these dual perspectives and identify potential needs. Collaborations between Somali communities, maternity care and social service providers can contribute with support to families in transition and bridge gaps to formal social and care services.